Vitamin D promotes MSC osteogenic differentiation stimulating cell adhesion and αVβ3 expression - Posa, Francesca; Cavalcanti-Adam, Elisabetta A. (Stem cells international, 2018)
Vitamin D (Vit D) by means of its biological active form, 1α,25-dihydroxyvitamin D3 (1,25(OH)2D3), has a protective effect on the skeleton by acting on calcium homeostasis and bone formation. Furthermore, Vit D has a direct effect on mesenchymal stem cells (MSCs) in stimulating their osteogenic differentiation. In this work, we present for the first time the effect of 1,25(OH)2D3 on MSC adhesion. Considering that cell adhesion to the substrate is fundamental for cell commitment and differentiation, we focused on the expression of αVβ3 integrin, which has a key role in the commitment of MSCs to the osteoblastic lineage. Our data indicate that Vit D increases αVβ3 integrin expression inducing the formation of focal adhesions (FAs). Moreover, we assayed MSC commitment in the presence of the extracellular matrix (ECM) glycoprotein fibronectin (FN), which is able to favor cell adhesion on surfaces and also to induce osteopontin (OPN) expression: this suggests that Vit D and FN synergize in supporting cell adhesion. Taken together, our findings provide evidence that Vit D can promote osteogenic differentiation of MSCs through the modulation of αVβ3 integrin expression and its subcellular organization, thus favoring binding with the matrix protein (FN).
Gesehen am 08.05.2020